(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY/PRINCIPLES: To assess the usefulness of several laboratory and radiological investigations for the limping child with suspected transient synovitis of the hip. METHODS: The medical records of children admitted at our children’s hospital for nontraumatic hip pain between 1999 and 2007 were retrospectively reviewed. During the study period, all children without a definite diagnosis after routine investigations in the emergency department were admitted and a specific work-up including antinuclear antibodies titre, rheumatoid factor, antistreptolysin O titre, Lyme disease serology and hip ultrasonography were obtained. Children were systematically re-evaluated 6 weeks after hospital discharge, with a clinical examination and radiological hip views. Patients were diagnosed with transient synovitis of the hip if an ultrasound-confirmed hip effusion was present at time of admission, complete resolution of symptoms occurred without any specific treatment, and no other pathology of the hip was identified during follow-up. RESULTS: A total of 417 cases without definite diagnosis were admitted and were submitted to a specific work-up. Transient synovitis of the hip was subsequently diagnosed in 383 patients, septic arthritis in 1 patient, and Lyme arthritis in 1 patient. Thirty-two patients remained without diagnosis. No rheumatological condition was found. CONCLUSION: Our results suggest that most investigations performed during the initial work-up in patients suspected transient synovitis of the hip are unnecessary and should routinely include only white blood cell count, C-reactive protein, erythrocyte sedimentation rate, and hip radiography and ultrasonography. No further investigations are necessary during follow-up for transient synovitis of the hip in asymptomatic children.